Use and Awareness of E-Resources by Postgraduate Students of the Faculty of Social Sciences, Barkatullah University, Bhopal: A Survey (LIS TODAY, 2024)
The study investigates the use and awareness of e-resources among postgraduate  students in the Faculty of Social Sciences at Barkatullah University, Bhopal.  E-resources, such as online journals, databases, and digital libraries, have become  increasingly important in academic research and learning. This paper aims to  assess the level of awareness, access, and utilization of e-resources by postgraduate  students, as well as identify the barriers and challenges they face. The study  employed a survey-based methodology, involving a structured questionnaire  distributed to a sample of 110 postgraduate students across various departments  within the Faculty of Social Sciences. The findings reveal a moderate level of  awareness and utilization of e-resources among the respondents.
Keywords: E-resources; Online resources; Postgraduate students; Faculty of Social Sciences; Barkatullah University